Students’ beliefs on mathematics and achievement of university students: logistics regression analysis - Suthar, Velo; Ahmad Tarmizi, Rohani; Midi, Habshah; Adam, Mohd Bakri (Elsevier, 2010)
At present, after almost more than 20-decades, Malaysia can boast of a solid National Philosophy of Education, despite tremendous struggles and hopes. Continuous professional learning opportunities are provided to students in order to enhance, support and sustain the students’ mathematics ability. Much evidence had shown that students’ beliefs in mathematics are central in developing students’ career in mathematics related areas. In addition mathematical beliefs are closely correlated to their mathematics ability among students. However, few literatures had been found related to this phenomenon among university undergraduate students. The present study involves a sample of university undergraduate mathematicsstudents, who had completed a self-reported questionnaire related to student mathematical beliefs on three dimensions, such as: beliefs about mathematics, beliefs about importance of mathematics and beliefs about one's ability in mathematics. The authors examined students’ mathematical beliefs based on logisticregression model estimation technique, appropriate for a survey design study. The results illustrated and identified significant relationships between students’ beliefs about importance of mathematics and beliefs about one's ability in mathematics with mathematics ability. In addition, the overall model explained further that 74.6% of the sample was classified correctly.